Hubungan Motivasi Terhadap Hasil Belajar Pendidikan Pancasila Bagi Siswa Kelas V Sekolah Dasar Islam Terpadu Kota Padang - Rahmi, Aulia; Waldi, Atri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
This study aimed to identify the correlation between learning motivation and learning outcomes in Pancasila and Civic Education of fifth-grade students of SDIT Nurul Ikhlas Kota Padang. This study used a correlational study with a quantitative approach. The population of the study was all the fifth-grade students of SDIT Nurul Ikhlas Kota Padang academic year 2023/2024 which consisted of 43 students. The sampling technique applied in the study was total sampling, as a result, the number of samples was the same as the number of the population. The data were collected through the instrument in the form of a questionnaire about learning motivation and also the documentation of students’ daily test scores for Pancasila and Civic Education subjects. The computer program SPSS (Statistical Package for the Social Sciences) 25 version was used with the Pearson Correlation Product Moment as the technique to analyze the data. The result showed that there is a positive and significant correlation between learning motivation and learning outcomes in Pancasila Civic Education with rcount > rtable (0,0568 >0,301) in a significance level of 5%. Therefore, it can be concluded that the higher the level of learning motivation, the better the learning outcomes in Pancasila and Civic Education subject